Issues of Khiyar (option) in housing agreements in Peninsular Malaysia - Md Dahlan, Nuarrual Hilal (Malayan Law Journal, 2014)
It is well entrenched in lslamic Law that khiyar is an inherent right of the contracting parties in a contract.This right provides the contracting parties with a right of option to void the contract they entered into if the subject matter of the contract does not comply with the specifications, terms and conditions of the contract.In Peninsular Malaysia, all house purchasers who wish to buy houses built by the licensed housing developers who are subject to the Housing Development (Control and Licensing) Act 1966 (Act 118) and subject to the control of the Ministry of Housing and Local Government (MHLG) are required to use the prescribed housing statutory standard sale and purchase agreements as contained in Schedules G, H, I and J ('the said agreements').However after close scrutiny over the said agreements, there is no term of khiyar provided.Thus, due to the absence of term of khiyar in the said agreements, the said agreements, it is submitted, are null and void under lslamic Law. Likewise, it follows that due to this nullity, the subsequent housing transactions involving loan agreements, effected through Bai' Bithaman al-Ajil (BBA), Musharakah Mutanaqisah, ljarah Thamma a/-Bay' and Istisna' used by lslamic banks, may also be affected and are void.This academic paper is a fruit of a completed research undertaken by the author.Its objective is to discuss and explore the issues of khiyar in the said agreements, particularly when the housing projects are abandoned.The author used qualitative legal research methodology to unravel the issues of khiyar in the said agreements.This paper contends that due to the absence of khiyar in the said agreements, the said agreements have not complied with the requirements under lslamic law and could cause the housing transactions and the subsequent loan transactions entered into by the purchasers/borrower, developers and lslamic banks, void too.This paper also provides certain proposals to improve the current terms and conditions in the said agreements in order to render them harmonious with the spirit and intent of lslamic law.